2018
DOI: 10.1080/02705060.2017.1391722
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and roles of Microcystis extracellular polymeric substances (EPS) in cyanobacterial blooms: a short review

Abstract: Cyanobacterial blooms are serious eco-environmental problem, and cyanobacteria can produce large amounts of extracellular polymeric substances (EPS). EPS, as complex polymers, possess several characteristics, such as hydrophobicity, carbon-rich, nutrient-rich, metal adsorption, and stickiness, which influence the cell surface characteristics and the cycling of carbon, nutrients, metals, and rheological property in water, particularly during large blooms. All these characteristics are related to bloom outbreak.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 66 publications
0
41
0
Order By: Relevance
“…Finally, it is necessary to mention that in natural environments the cells of M. aeruginosa are normally found forming colonies, which are more protected from the external environment than single cells because they are embedded in extracellular polymeric substances (EPS, Liu et al 2018). Therefore, taking into account that the experiments in this study were performed with single-celled culture inoculums, we would surely be underestimating the capacity of adaptation of the population in nature.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, it is necessary to mention that in natural environments the cells of M. aeruginosa are normally found forming colonies, which are more protected from the external environment than single cells because they are embedded in extracellular polymeric substances (EPS, Liu et al 2018). Therefore, taking into account that the experiments in this study were performed with single-celled culture inoculums, we would surely be underestimating the capacity of adaptation of the population in nature.…”
Section: Discussionmentioning
confidence: 97%
“…When these layers are present in cyanobacteria, they are likely to perform a protective role against ultraviolet radiation, oxidation, toxic compounds, desiccation and predation by protozoans [14]. More specifically, studies have shown that these external layers are essential for maintaining the colonial morphology of cyanobacteria, and they participate in a wide array of physiological processes, including cell-to-cell interactions, adhesion and aggregation, which further influence the fate of blooms [15]. Cyanobacterial external layers exhibit some typical characteristics that provide a competitive advantage over other competitors throughout its life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…EPS are crucial for the development of biofilms, providing fundamental cohesive force for the colonization of solid surfaces (Liu et al, 2018). Our findings suggest that exopolysaccharides of the EPS layer substantially inhibit EET processes by increasing charge transfer resistance.…”
Section: Resultsmentioning
confidence: 99%